How reliable are the statistics for the stability and growth pact ? - Mora, Luis Gordo; Martins, Joao Nogueira; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
The aim of this paper is to assess the reliability of the government deficit and debt figures reported to the European Commission by Member States. Reliability is one of the several dimensions of quality in statistics; it refers to the magnitudes of data revisions after the publication of the first outcomes. The measurement of the data reliability and inference about potential future revisions are particularly relevant for fiscal surveillance in the EU since statistical institutes take a long time - usually four years - to provide final data, while the decisions on the Stability and Growth Pact context are taken on the basis of the first estimates available shortly after the end of each year. The paper shows that there are very significant differences in reliability among Member States and indicates the margins of uncertainty in relation to the most recent years' data. It also compares the reliability of deficit and debt figures; checks that the shift from ESA79 to ESA95 did not generally harm the reliability of data and suggests that the size of deficits may have an impact on the way statistical offices revise data.
Economic Papers